High-elastic material for anti-slip sole and preparation method of high-elastic material
By modifying polyurethane and silicone rubber composite materials, the problems of insufficient elasticity, anti-slip performance and weather resistance of traditional shoe sole materials have been solved, and a shoe sole material with high elasticity, durable anti-slip and wear resistance has been achieved, which is suitable for sports and outdoor use.
Patent Information
- Application Number
- CN202511374592.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-25
- Publication Date
- 2025-10-28
AI Technical Summary
Traditional shoe sole materials are inadequate in terms of elasticity, slip resistance, weather resistance, and abrasion resistance, especially in sports and outdoor use scenarios, and existing improvement methods are difficult to meet the needs of all-weather wear.
A composite material of modified polyurethane and modified silicone rubber is used. Through vacuum dehydration, isocyanate reaction and graft modification, a cross-linked network of flexible segments and polar groups is formed. Combined with calcium carbonate filler and naphthenic oil, a material with high elasticity, excellent weather resistance and anti-slip properties is formed.
It achieves high elasticity and durable anti-slip performance of the material, significantly improves weather resistance and wear resistance, maintains good support and anti-slip ability during long-term use, and extends the service life of the sole.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a high-elastic material for anti-slip shoe soles and its preparation method. Background Technology
[0002] As the core functional component of a shoe, the performance of the sole directly affects the wearing experience and safety. Traditional sole materials mostly rely on basic polymer materials such as ordinary rubber and EVA foam. While these provide basic elastic support, they have gradually revealed several key defects in actual use. Ordinary rubber, due to its relatively simple molecular chain structure, is prone to irreversible plastic deformation after long-term pressure or repeated bending, resulting in problems such as collapse in the middle of the sole and curling at the edges. Especially in sports scenarios, frequent jumping and sudden stops can lead to a rapid decrease in support, affecting not only gait stability but also exacerbating foot fatigue. While EVA foam is lightweight and soft, it has obvious "stress relaxation" characteristics. Its rebound rate decreases significantly over time after being compressed, and it is prone to hardening and cracking in low-temperature environments, making it difficult to meet the needs of all-weather wear.
[0003] As a core safety indicator for shoe soles, anti-slip performance is particularly challenging due to the limitations of traditional materials. Ordinary rubber has a simple chemical composition, and its coefficient of friction with the ground is greatly affected by the environment. While the coefficient of friction is acceptable in a dry state, it drops sharply when exposed to water, oil, or dust, as liquids or particles fill the surface's micro-textures. EVA foam, on the other hand, has low surface energy and insufficient hardness, making it difficult to form an effective grip, leading to a "slip delay" phenomenon on wet surfaces. More importantly, the anti-slip structures on traditional materials are often simple textured patterns. Over time, wear debris accumulates and covers the surface, further weakening the anti-slip effect and requiring frequent sole replacements. This rapid decline in anti-slip performance, especially in high-frequency outdoor and sports settings, directly increases safety hazards and raises operating costs.
[0004] Furthermore, the weather resistance and abrasion resistance of traditional shoe sole materials are insufficient for long-term use. Ordinary rubber is prone to oxidative degradation in environments with ultraviolet radiation and high humidity, causing molecular chain breakage, hardening, cracking, and loss of elasticity. EVA foam, due to its high hygroscopicity, absorbs moisture and expands in humid environments, leading to mold growth and delamination after its internal structure is damaged. Simultaneously, friction from the ground during daily wear accelerates surface wear, causing not only aesthetic aging but also loosening of the internal structure and reducing overall strength. While existing improvement methods attempt to enhance performance by adding fillers or surface coatings, they often face the contradiction of "elasticity-slip resistance." Adding fillers reduces elasticity, while surface coatings are prone to peeling and failure. Moreover, improvements in weather resistance largely rely on chemical stabilizers, which still experience performance degradation after long-term use, failing to meet the market's urgent demand for high-performance shoe soles. Summary of the Invention
[0005] The purpose of this invention is to provide a high-elastic material for anti-slip shoe soles and its preparation method, which solves the problems of insufficient elasticity, easy degradation of anti-slip performance, weak weather resistance and low wear resistance of traditional shoe soles.
[0006] The present invention achieves the above objectives through the following technical solutions: A highly elastic material, by mass percentage, comprises the following raw materials: Modified polyurethane: 30-50%; Modified silicone rubber: 20-40%; Calcium carbonate: 10-20%; Dicumyl peroxide: 1-3%; 2-Mitrol-benzothiazole: 0.5-1.5%; N-Isopropyl-N'-Phenylene-p-phenylenediamine: 0.5-1%; Naphthenic oil: 1-5%; The method for preparing the modified polyurethane includes: A1, vacuum dehydrating polybutylene adipate at 110-115℃, cooling to 60-65℃ and then adding toluene diisocyanate and stirring to obtain a terminal isocyanate prepolymer; A2, then adding dimethylolpropionic acid to the prepolymer and heating to 80-85℃ to react; then adding triethylamine and adding deionized water while stirring to obtain an aqueous polyurethane dispersion; then adding methyl methacrylate, hydroxyethyl acrylate and potassium persulfate to the dispersion and heating to 70-75℃ to react.
[0007] According to a preferred embodiment of the present invention, the polybutylene adipate was purchased from Wanhua Chemical Group Co., Ltd., and the product name is WANOL® 450B (molecular weight about 2000, hydroxyl value 56-60mgKOH / g).
[0008] According to a preferred embodiment of the present invention, the toluene diisocyanate was purchased from Wanhua Chemical Group Co., Ltd., and the product type was TDI-80 (purity ≥99.5%, freezing point 13℃).
[0009] According to a preferred embodiment of the present invention, the terminal isocyanate prepolymer was purchased from Jiangsu Hengxiang Technology Co., Ltd., and the model is PE-2000 (NCO content 3.8±0.2%, viscosity 500-800mPa·s (25℃)).
[0010] According to a preferred embodiment of the present invention, the dimethylolpropionic acid was purchased from Dandong Fine Chemicals Factory, and the product name is DMPA-99 (purity ≥99%, moisture ≤0.05%).
[0011] According to a preferred embodiment of the present invention, the triethylamine was purchased from Jiangsu Feixiang Chemical Co., Ltd., and the model was TEA-99 (purity ≥99.5%, moisture ≤0.03%).
[0012] According to a preferred embodiment of the present invention, the methyl methacrylate was purchased from Wanhua Chemical Group Co., Ltd., and the product name is WANOL® MMA (purity ≥99.8%, polymerization inhibitor MEHQ content ≤200ppm).
[0013] According to a preferred embodiment of the present invention, the hydroxyethyl acrylate was purchased from Jiangsu Sanmu Group Co., Ltd., and the model is SM-350 (purity ≥99.5%, moisture ≤0.1%).
[0014] According to a preferred embodiment of the present invention, the potassium persulfate was purchased from Shanghai Shisihewei Chemical Co., Ltd., and the model is KPS-99 (purity ≥99.2%, active oxygen content ≥4.5%).
[0015] According to a preferred embodiment of the present invention, the deionized water is purchased from Shanghai Binrun Environmental Protection Technology Co., Ltd., and the model is DI-100 (resistivity ≥10MΩ·cm, conductivity ≤0.1μS / cm).
[0016] In the preparation of the modified polyurethane of this invention, polybutylene adipate (PBA) is first vacuum dehydrated at 110-115°C. The terminal hydroxyl groups (-OH) on its molecular chain undergo an addition reaction with the -NCO groups of toluene diisocyanate (TDI) to form a terminal isocyanate prepolymer. This process is a typical polyurethane prepolymerization reaction. The two -NCO groups of TDI react sequentially with the two -OH groups of PBA to generate a polymer chain linked by linear urethane bonds (-NHCOO-). Subsequently, the -COOH groups of dimethylolpropionic acid (DMPA) are added to continue the reaction with the remaining -NCO groups in the prepolymer, increasing the molecular chain length through chain extension. Introducing a carboxyl group (-COOH) allows it to neutralize with subsequent triethylamine (TEA) to form an ammonium salt, imparting aqueous dispersibility. Adding deionized water causes the ammonium salt to hydrolyze, allowing the polyurethane chains to expand and form a stable aqueous dispersion. Further addition of methyl methacrylate (MMA), hydroxyethyl acrylate (HEA), and potassium persulfate causes potassium persulfate to decompose and generate free radicals that initiate monomer polymerization. The double bonds (C=C) of MMA and HEA open under the influence of these free radicals, undergoing graft copolymerization with active hydrogen atoms (such as -NH- or -OH) on the polyurethane chains to form modified polyurethane with acrylate grafted groups, thus enhancing surface polarity and reactivity.
[0017] According to a preferred embodiment of the present invention, in step A1, the vacuum dehydration time is 2-3 hours; the stirring reaction time is 2-3 hours.
[0018] According to a preferred embodiment of the present invention, in step A2, the temperature is raised to 80-85°C and the reaction is carried out for 1-1.5 hours; the stirring speed is 8000-8500 rpm, and the reaction time is raised to 70-75°C for 3-4 hours.
[0019] According to a preferred embodiment of the present invention, the method for preparing the modified silicone rubber includes: adding methyl vinyl silicone rubber and precipitated silica to a mixer and mixing them at 120-125°C; adding hydroxyl silicone oil and passing it through a thin sheet; crushing the mixed rubber into particles; adding γ-glycidoxypropyltrimethoxysilane and ultrasonically dispersing it at 80-85°C; and then mixing the modified silicone rubber particles with ethylenediamine and tetraethyl orthosilicate and vulcanizing them at 150-155°C.
[0020] According to a preferred embodiment of the present invention, the mixing time is 15-20 min; the number of thin passes is 5-6; the mixed rubber is crushed into 20-25 mesh particles; the ultrasonic dispersion time is 30-35 min; and the vulcanization time is 40-45 min.
[0021] According to a preferred embodiment of the present invention, the methyl vinyl silicone rubber was purchased from Chenhua Technology Co., Ltd., and the model is MR-107 (molecular weight of about 500,000, vinyl content of 0.1-0.3%). According to a preferred embodiment of the present invention, the precipitated silica was purchased from Quecheng Silicon Chemical Co., Ltd., and the model is QS-102 (specific surface area 200±20m² / g, silica content ≥99%). According to a preferred embodiment of the present invention, the internal mixer was purchased from Dalian Rubber & Plastics Machinery Co., Ltd., and the model is X(S)M-500 / 400 (capacity 500L, power 37kW, suitable for mixing rubber materials). According to a preferred embodiment of the present invention, the hydroxyl silicone oil is purchased from Zhejiang Xin'an Chemical Group Co., Ltd., and the model is 201-50 (viscosity 50-60 mPa·s (25℃), hydroxyl content ≥8%). According to a preferred embodiment of the present invention, the γ-glycidyl etheroxypropyltrimethoxysilane was purchased from Danyang Organosilicon Materials Industry Co., Ltd., and the model number is A-187 (purity ≥98%, epoxy content ≥9.5%). According to a preferred embodiment of the present invention, the ethylenediamine was purchased from Jiangsu Feixiang Chemical Co., Ltd., and the product name was EDA-99 (purity ≥99.5%, moisture ≤0.03%). According to a preferred embodiment of the present invention, the tetraethyl orthosilicate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and the model is TEOS-01 (purity ≥99.0%, boiling point 168-170℃).
[0022] In the preparation of the modified silicone rubber of this invention, when methyl vinyl silicone rubber (VMQ) and precipitated silica (specific surface area 200 m² / g) are mixed at 120-125℃, the silanol groups (-SiOH) on the surface of the silica and the -Si-O- groups of the silicone rubber backbone initially combine through hydrogen bonding. Some silanol groups undergo dehydration condensation to form Si-O-Si covalent bonds, enhancing the reinforcing effect. After adding hydroxyl silicone oil (molecular weight 3000) to adjust the viscosity of the system and passing it through a thin tube 5 times, the silicone oil molecular chains insert into the silicone rubber network, improving flexibility. After being crushed into 20-25 mesh particles, the epoxy groups of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) are... (-Ethylene oxide) undergoes a condensation reaction (removal of methanol) with the residual silanol groups on the surface of silica or the hydroxyl groups on the surface of silicone rubber to generate epoxy-modified silicone rubber particles. The epoxy groups (-CH(O)CH-) provide active sites for subsequent crosslinking. Subsequently, it is mixed with ethylenediamine and tetraethyl orthosilicate. The amino group (-NH2) of ethylenediamine undergoes a ring-opening reaction with the epoxy group of KH-560 to generate amine bonds (-NH-CH2CH(OH)-CH2-). At the same time, tetraethyl orthosilicate hydrolyzes to generate silanols. The silanols further condense with each other or with the -Si-O- segments of silicone rubber and the amino group of ethylenediamine to form a three-dimensional network crosslinked structure, which gives the material high elasticity and weather resistance.
[0023] The present invention also provides a method for preparing the aforementioned high-elasticity material, comprising the following steps: S1. Preheat the modified polyurethane at 80-85℃, and then add it together with the modified silicone rubber to a high-speed mixer for preliminary mixing. During the preliminary mixing process, add calcium carbonate and naphthenic oil in sequence and continue mixing. After the materials are mixed, transfer them to a two-roll mill for thin-pass processing. S2, then dicumyl peroxide, 2-thiol benzothiazole, and N-isopropyl-N'-phenyl-p-phenylenediamine are added to the open mill and refining. S3. Finally, transfer the compound to a flat vulcanizing machine for vulcanization, cool it to 20-25℃, and cut it into shape.
[0024] In the preparation of the high-elasticity material of this invention, when modified polyurethane (containing acrylate polar groups) and modified silicone rubber (containing epoxy crosslinking network) are mixed in a certain proportion, the flexibility of the polyurethane chain segments and the compliance of the silicone rubber chain segments form a complementary network through physical entanglement; calcium carbonate, as a filler, interacts with the -COO group of the polyurethane through its surface hydroxyl groups. -The -Si-OH groups of silicone rubber form weak interfacial bonds, while naphthenic oils (cyclic hydrocarbons) embed between polymer chains to reduce intermolecular forces and improve processing fluidity. Dicumyl peroxide (DCP) decomposes to generate free radicals, which initiate cross-linking reactions of the urethane bonds (-NHCOO-) of polyurethane, the -Si-O- bonds of silicone rubber, and the surface hydroxyl groups of fillers, forming additional CC or Si-C cross-linking points. 2-Mitol-benzothiazole (accelerator M) accelerates the free radical transfer of DCP through sulfur atom transfer, shortening the vulcanization time. N-isopropyl-N'-phenyl-p-phenylenediamine (antioxidant 4010NA) inhibits thermo-oxidative aging by capturing free radicals. Finally, after vulcanization in a flat vulcanizing machine (160℃, 10MPa), the components form a uniform and continuous high-elastic composite material through chemical cross-linking and physical entanglement, which has high elasticity, durable anti-slip properties, and weather and wear resistance.
[0025] According to a preferred embodiment of the present invention, in step S1, the preheating time is 10-15 min; the speed of the high-speed mixer is 1000-1200 rpm, the initial mixing time is 5-10 min; the continued mixing time is 3-5 min; the roll temperature of the two-roll open mill is 80-85℃; the roll gap of the thin pass treatment is 1-1.2 mm, and the number of thin passes is 3-4 times.
[0026] According to a preferred embodiment of the present invention, in step S2, the turning time in the open mill is 8-10 minutes.
[0027] According to a preferred embodiment of the present invention, in step S3, the vulcanization temperature in the flat vulcanizing machine is 160-165°C, the pressure is 10-12 MPa, and the vulcanization time is 15-20 min.
[0028] The present invention also provides an application of the high-elasticity material described above or the high-elasticity material prepared by the preparation method described above in anti-slip shoe soles.
[0029] The beneficial effects of this invention are as follows: The high-elastic material described in this invention significantly improves its overall performance through the synergistic effect of modified components and preparation process, effectively addressing the performance shortcomings of traditional shoe sole materials. Its core advantages are reflected in the following three aspects: Firstly, the material possesses excellent high elasticity and long-lasting resilience. The modified polyurethane uses polybutylene adipate as the soft segment base, and through vacuum dehydration, isocyanate reaction, and graft modification, it forms a network structure cross-linked with flexible segments and polar groups (such as acrylates), giving the material excellent deformation recovery ability. The modified silicone rubber, reinforced with silica and toughened with hydroxyl silicone oil, enhances the flexibility of the segments. When the two are compounded in a specific ratio, their softness and hardness complement each other. Combined with the appropriate reinforcement of calcium carbonate filler and the plasticizing adjustment of naphthenic oil, the material can respond quickly and rebound under pressure. Even after long-term wear or repeated bending, it is not prone to collapse or curling, effectively maintaining the support and comfort of the shoe sole.
[0030] Secondly, the material achieves durable and stable anti-slip performance. The polar acrylate groups on the modified polyurethane surface complement the epoxy groups exposed after modification with a silane coupling agent in the modified silicone rubber. The former increases polar adsorption with the ground, while the latter reduces surface energy to form microscopic interlocking, jointly constructing a stable friction interface in both dry and wet conditions. The coefficient of friction is significantly higher than that of ordinary materials in the dry state, and it still maintains a high coefficient of friction after wetting or contamination (such as water or oil). Furthermore, the modified surface structure is not easily covered by abrasive debris, and the rate of decrease in the coefficient of friction over time is greatly reduced, ensuring the continuous anti-slip capability of the sole in complex ground environments.
[0031] Thirdly, the material exhibits excellent weather resistance and abrasion resistance. Modified polyurethane, through end-group sealing and polyurethane chain segment protection, effectively inhibits UV-induced oxidative degradation; the saturated main chain structure of modified silicone rubber reduces the risk of aging in humid and hot environments. The combination of these two materials significantly improves overall UV resistance and humid heat resistance, making it less prone to hardening or cracking after long-term exposure or use. Simultaneously, the synergistic effect of the high-elasticity structure and filler enhances the material's abrasion resistance, preventing deep grooves or peeling from forming on the surface due to friction, resulting in a very low Akron abrasion rate and significantly extending the lifespan of the shoe sole. Detailed Implementation
[0032] The following detailed embodiments are only used to further illustrate this application and should not be construed as limiting the scope of protection of this application. Those skilled in the art can make some non-essential improvements and adjustments to this application based on the above application content.
[0033] I. Implementation Examples
[0034] Example 1
[0035] Raw material composition: 40g modified polyurethane, 30g modified silicone rubber, 15g calcium carbonate, 2g dicumyl peroxide, 1g 2-thiol benzothiazole, 0.8g N-isopropyl-N'-phenyl-p-phenylenediamine, 3g naphthenic oil.
[0036] Preparation of modified polyurethane: WANOL® 450B polybutylene adipate (molecular weight 2000) produced by Wanhua Chemical was used as the soft segment base material. It was placed in a vacuum drying oven and dehydrated at 110℃ for 2 hours until the moisture content of the material dropped below 0.05%. After dehydration, the material was cooled to 60℃, and 45g of TDI-80 toluene diisocyanate produced by Wanhua Chemical was added. The mixture was mechanically stirred at 200 rpm for 2 hours to form a terminal isocyanate prepolymer. Subsequently, 3g of DMPA-99 dimethylolpropionic acid produced by Dandong Fine Chemicals Factory was added to the prepolymer, and the temperature was raised to 80℃ and maintained at a constant temperature. The reaction was carried out at 150 rpm for 1 hour to further extend the molecular chain. After the reaction was completed, 3.3g of TEA-99 triethylamine produced by Jiangsu Feixiang Chemical Co., Ltd. was added, and the carboxyl groups in the prepolymer were neutralized by rapid stirring until the pH of the system reached 8-9. After neutralization, the material is transferred to a high-speed disperser and stirred at 8000 rpm. Simultaneously, 200g of DI-100 deionized water (produced by Shanghai Binrun Environmental Protection Technology Co., Ltd.) is slowly added, and stirring is continued for 10 minutes to form a stable aqueous polyurethane dispersion. 100g of the above aqueous polyurethane dispersion is then added to 15g of WANOL® MMA methyl methacrylate (produced by Wanhua Chemical), 5g of SM-350 hydroxyethyl acrylate (produced by Jiangsu Sanmu Group Co., Ltd.), and KPS-99 potassium persulfate (produced by Shanghai Shisihewei Chemical Co., Ltd.). The mixture is heated to 70℃ and reacted for 3 hours to complete the graft copolymerization reaction, yielding the modified polyurethane.
[0037] Preparation of modified silicone rubber: 100g of MR-107 methyl vinyl silicone rubber (manufactured by Chenhua Technology Co., Ltd.) and 20g of QS-102 precipitated silica (manufactured by Quecheng Silicon Chemical Co., Ltd.) were mixed in an X(S)M-500 / 400 internal mixer (manufactured by Dalian Rubber & Plastics Machinery Co., Ltd.) at 120℃ for 15 minutes. During the mixing process, 3g of 201-50 hydroxyl silicone oil (manufactured by Zhejiang Xin'an Chemical Group Co., Ltd.) was added to adjust the viscosity. After passing through a thin filter five times, the mixture was sheeted. The mixed rubber was crushed into 20-mesh particles and then A-187 γ-glycidyl etheroxypropyltrimethoxysilane (manufactured by Danyang Organosilicon Materials Industry Co., Ltd.) was added and ultrasonically dispersed at 80℃ for 30 minutes. The dispersed particles were then mixed with 0.5g of EDA-99 ethylenediamine produced by Jiangsu Feixiang Chemical Co., Ltd. and 1g of TEOS-01 tetraethyl orthosilicate produced by Shanghai Aladdin Biochemical Technology Co., Ltd. The mixture was transferred to a vulcanizing machine and vulcanized at 150℃ and 10MPa for 40 minutes to obtain modified silicone rubber.
[0038] Preparation of high-elasticity material: The prepared modified polyurethane was placed in an oven and preheated at 80℃ for 10 minutes to enhance fluidity. Then, the preheated modified polyurethane and modified silicone rubber were added to a high-speed mixer at 1000 rpm for initial mixing for 5 minutes. During mixing, 15g of calcium carbonate and naphthenic oil (produced by Karamay Petrochemical Company, viscosity 100-120 mPa·s) were added sequentially, and mixing continued for 3 minutes. After the material was homogeneous, it was transferred to a two-roll mill (roll temperature 80℃, roll gap 1mm) and passed through a thin mill three times to further disperse the filler and plasticizer. After the thin milling, 2g of dicumyl peroxide, 1g of 2-thiol benzothiazole, and 0.8g of N-isopropyl-N'-phenyl-p-phenylenediamine were added to the two-roll mill and milled for 8 minutes to ensure the compounding agents were uniformly coated into the rubber matrix. Finally, the compounded rubber is transferred to a flat vulcanizing machine (temperature 160℃, pressure 10MPa) for vulcanization for 15 minutes. After cooling to 25℃, it is cut into shape to obtain the target high-elasticity material.
[0039] Example 2
[0040] The preparation method is the same as in Example 1, except that the raw material composition is as follows: 35g modified polyurethane, 35g modified silicone rubber, 12g calcium carbonate, 1.5g dicumyl peroxide, 0.8g 2-thiol benzothiazole, 0.6g N-isopropyl-N'-phenyl-p-phenylenediamine, and 2g naphthenic oil.
[0041] Preparation of modified polyurethane: 100g of WANOL® 450B polybutylene adipate (molecular weight 2000) produced by Wanhua Chemical was vacuum dehydrated at 110℃ for 2 hours. The temperature was then lowered to 60℃, and 35g of TDI-80 toluene diisocyanate produced by Wanhua Chemical was added. The mixture was stirred and reacted for 2 hours to obtain a terminal isocyanate prepolymer. Subsequently, 2.6g of dimethylolpropionic acid (Dandong DMPA-99) and 2.8g of triethylamine (Jiangsu Feixiang TEA-99) were added for neutralization. After dispersion with water, 87.5g of the corresponding proportion of aqueous polyurethane dispersion was added to 11.25g of methyl methacrylate (WANOL® MMA), 3.75g of hydroxyethyl acrylate (Jiangsu Sanmu SM-350), and 0.175g of potassium persulfate (Shanghai Shisihewei KPS-99). The mixture was reacted at 70℃ for 3 hours to obtain the modified polyurethane.
[0042] Preparation of modified silicone rubber: 87.5g of MR-107 methyl vinyl silicone rubber (produced by Chenhua Technology Co., Ltd.) and 17.5g of QS-102 precipitated silica (produced by Quecheng Silicon Chemical Co., Ltd.) were mixed in an X(S)M-500 / 400 internal mixer (produced by Dalian Rubber & Plastics Machinery Co., Ltd.) at 120℃ for 15 minutes. Then, 2.6g of 201-50 hydroxyl silicone oil (produced by Zhejiang Xin'an Chemical Group Co., Ltd.) was added and passed through a thin pass 5 times before sheeting. The sheets were then crushed into 20-mesh particles and mixed with 2.6g of A-187 γ-glycidyl etheroxypropyltrimethoxysilane (produced by Danyang Organosilicon Materials Industry Co., Ltd.). The mixture was ultrasonically dispersed at 80℃ for 30 minutes. Finally, it was mixed with 0.44g of EDA-99 ethylenediamine (produced by Jiangsu Feixiang Chemical Co., Ltd.) and 0.7g of TEOS-01 tetraethyl orthosilicate (produced by Shanghai Aladdin Biochemical Technology Co., Ltd.), and vulcanized at 150℃ for 40 minutes to obtain the modified silicone rubber.
[0043] Preparation of high-elasticity material: Modified polyurethane is preheated at 80℃ for 10 minutes, and mixed with modified silicone rubber in a high-speed mixer (1000rpm) for 5 minutes. Then, 12g of calcium carbonate and 2g of naphthenic oil are added and mixed for another 3 minutes. The mixture is then transferred to a two-roll mill (80℃, 1mm gap) and passed through three times. 1.5g of dicumyl peroxide, 0.8g of 2-thiol benzothiazole, and 0.6g of N-isopropyl-N'-phenyl-p-phenylenediamine are added and the mixture is kneaded for 8 minutes. The mixture is then vulcanized in a flat vulcanizing machine (160℃, 10MPa) for 15 minutes and cooled to 25℃ before being cut into shape.
[0044] Example 3
[0045] The preparation method is the same as in Example 1, except that the raw material composition is as follows: 45g modified polyurethane, 25g modified silicone rubber, 18g calcium carbonate, 2.5g dicumyl peroxide, 1.2g 2-thiol benzothiazole, 1g N-isopropyl-N'-phenyl-p-phenylenediamine, and 4g naphthenic oil.
[0046] Preparation of modified polyurethane: 100g of WANOL® 450B polybutylene adipate (molecular weight 2000) produced by Wanhua Chemical was vacuum dehydrated at 110℃ for 2 hours. The temperature was then lowered to 60℃, and 45g of TDI-80 toluene diisocyanate produced by Wanhua Chemical was added. The mixture was stirred and reacted for 2 hours to obtain a terminal isocyanate prepolymer. Subsequently, 3.4g of dimethylolpropionic acid (Dandong DMPA-99) and 3.7g of triethylamine (Jiangsu Feixiang TEA-99) were added for neutralization. After dispersion with water, 112.5g of the corresponding proportion of aqueous polyurethane dispersion was added to 16.9g of methyl methacrylate (WANOL® MMA), 5.6g of hydroxyethyl acrylate (Jiangsu Sanmu SM-350), and 0.22g of potassium persulfate (Shanghai Shisihewei KPS-99). The mixture was reacted at 70℃ for 3 hours to obtain the modified polyurethane.
[0047] Preparation of modified silicone rubber: 112.5g of MR-107 methyl vinyl silicone rubber (manufactured by Chenhua Technology Co., Ltd.) and 22.5g of QS-102 precipitated silica (manufactured by Quecheng Silicon Chemical Co., Ltd.) were mixed in an X(S)M-500 / 400 internal mixer (manufactured by Dalian Rubber & Plastics Machinery Co., Ltd.) at 120℃ for 15 minutes. Then, 3.4g of 201-50 hydroxyl silicone oil (manufactured by Zhejiang Xin'an Chemical Group Co., Ltd.) was added and passed through a thin pass 5 times before sheeting. The sheets were crushed into 20-mesh particles and then mixed with 3.4g of A-187 γ-glycidyl etheroxypropyltrimethoxysilane (manufactured by Danyang Organosilicon Materials Industry Co., Ltd.). The mixture was ultrasonically dispersed at 80℃ for 30 minutes. Finally, it was mixed with 0.58g of EDA-99 ethylenediamine (manufactured by Jiangsu Feixiang Chemical Co., Ltd.) and 1.2g of TEOS-01 tetraethyl orthosilicate (manufactured by Shanghai Aladdin Biochemical Technology Co., Ltd.), and vulcanized at 150℃ for 40 minutes to obtain the modified silicone rubber.
[0048] Preparation of high-elasticity material: Modified polyurethane is preheated at 80℃ for 10 minutes, and mixed with modified silicone rubber in a high-speed mixer (1000rpm) for 5 minutes. Then, 18g of calcium carbonate and 4g of naphthenic oil are added and mixed for another 3 minutes. The mixture is then transferred to a two-roll mill (80℃, 1mm gap) and passed through it 3 times. 2.5g of dicumyl peroxide, 1.2g of 2-thiol benzothiazole, and 1g of N-isopropyl-N'-phenyl-p-phenylenediamine are added and the mixture is re-rolled for 8 minutes. The mixture is then vulcanized in a flat vulcanizing machine (160℃, 10MPa) for 15 minutes and cooled to 25℃ before being cut into shape.
[0049] Comparative Example 1 The preparation method is the same as in Example 1, except that the raw material composition is: 40g of unmodified polyurethane (ordinary polyurethane), 30g of unmodified silicone rubber (ordinary silicone rubber), 15g of calcium carbonate, 2g of dicumyl peroxide, 1g of 2-thiol-benzothiazole, 0.8g of N-isopropyl-N'-phenyl-p-phenylenediamine, and 3g of naphthenic oil.
[0050] Comparative Example 2 The preparation method is the same as in Example 1, except that the raw material composition is: 30g of modified polyurethane (methyl methacrylate and hydroxyethyl acrylate are omitted in step A2), 40g of modified silicone rubber, 20g of calcium carbonate, 3g of dicumyl peroxide, 1.5g of 2-thiol-benzothiazole, 1g of N-isopropyl-N'-phenyl-p-phenylenediamine, and 5g of naphthenic oil. In the preparation of the modified polyurethane, only the terminal isocyanate prepolymer is reacted with dimethylolpropionic acid; graft copolymerization is not performed.
[0051] Comparative Example 3 The preparation method is the same as in Example 1, except that the material composition is: 40g modified polyurethane, 30g modified silicone rubber, 10g calcium carbonate, 1g dicumyl peroxide, 0.5g 2-thiol benzothiazole, 0.5g N-isopropyl-N'-phenyl-p-phenylenediamine, and 1g naphthenic oil.
[0052] II. Performance Testing The materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance testing according to the following methods: 1. Shore Hardness: According to GB / T 531.1-2008 "Test Method for Indentation Hardness of Vulcanized Rubber or Thermoplastic Rubber - Part 1: Shore Hardness Tester Method (Shore A)", use the LX-A type Shore hardness tester (accuracy ±0.5A) produced by Shanghai Liuzhong Measuring Instrument Factory. Under the conditions of room temperature (25±2℃) and relative humidity (65±5%), place the sample horizontally on the platform of the hardness tester, press the indenter vertically down to the specified depth (10±0.5mm), hold for 3 seconds and read the hardness value. Take the average value of the test at 5 different positions.
[0053] 2. Resilience: According to GB / T 1681-2018 "Determination of Resilience of Vulcanized Rubber", the Z010 universal testing machine manufactured by Zwick GmbH, Germany, was used to compress the sample by 50% (compression rate of 200 mm / min), hold for 2 seconds and then release it. The ratio of the height of the sample rebounding to the highest point to the height before compression was measured, and the average value of 3 tests was taken (expressed as a percentage).
[0054] 3. Coefficient of Friction: According to GB / T 10006-2021 "Determination of Coefficient of Friction of Plastic Films and Sheets", an FTM-2 friction coefficient tester manufactured by SMS Ltd. (UK) was used. The test conditions were: load 1N, sliding speed 0.5m / s, and contact area 20mm×20mm. Dry tests were conducted in a dry air environment (humidity ≤30%). Wet tests were conducted after soaking in deionized water for 1 hour (water temperature 25℃), removing the product, blotting the surface moisture with filter paper, and testing immediately. Each test consisted of 5 sliding operations, and the average value was taken.
[0055] 4. Akron abrasion: According to GB / T 1689-2014 "Test Method for Akron Abrasion of Vulcanized Rubber", the AK-1 Akron abrasion tester produced by Jiangdu Tiancan Test Machinery Factory was used. The sample size was 16mm×14mm×6mm, the standard load was 1.96N (applied by a 2kg weight), the speed was 40r / min, and it ran for 1.61km (about 4000 revolutions) on a standard rubber grinding wheel (Shore A hardness 75±5). After the test, the mass difference before and after abrasion was measured with an electronic balance (accuracy 0.0001g) and the abrasion amount (g / 1.61km) was calculated.
[0056] 5. Tensile strength retention rate after xenon lamp aging: According to GB / T 1865-2009 "Artificial climate aging and artificial radiation exposure (filtered xenon arc radiation) of paints and varnishes", a Q-SUN Xe-3 xenon lamp aging tester manufactured by Q-Lab Corporation of the United States was used. The irradiance was 550W / m² (at a wavelength of 340nm), the black panel temperature was 65±3℃, and the relative humidity was 50±5%. After continuous irradiation for 500 hours, the tensile strength was tested according to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" (sample size: 25mm×4mm×2mm, tensile rate 500mm / min), and the retention rate was calculated as (strength after aging / initial strength × 100%).
[0057] 6. Performance test results: Table 1: Performance test results of each embodiment and comparative example
[0058] As shown in Table 1, the test results of Examples 1-3 and Comparative Examples 1-3 indicate that the modification process significantly improves the overall performance of the high-elasticity material. In terms of Shore hardness, Examples 1-3 (55A, 53A, 58A) generally show higher hardness than Comparative Examples 1-3 (50A, 48A, 52A), with Example 3 exhibiting the highest hardness, reflecting the synergistic reinforcing effect of the modified polyurethane and silicone rubber. Regarding resilience, Examples 1-3 (68%, 70%, 66%) exceed Comparative Examples 1-3 (55%, 58%, 62%), indicating that the modified elastic network is more stable and has a stronger recovery ability under pressure.
[0059] Regarding the dry friction coefficient, Examples 1-3 (1.3, 1.25, 1.35) were significantly higher than Comparative Examples 1-3 (0.9, 1.1, 1.2), and the decrease in wet friction coefficient was even smaller (Example 1 wet 0.9 vs Comparative Example 1 wet 0.3), indicating that the polar groups (such as acrylates) on the surface of the modified material and the epoxy groups of the silicone rubber jointly improved the frictional stability under both dry and wet environments. As for Akron wear, Examples 1-3 (0.07, 0.065, 0.075 g / 1.61 km) were significantly lower than Comparative Examples 1-3 (0.12, 0.09, 0.11 g / 1.61 km), verifying the synergistic effect of the high elasticity of the modified silicone rubber and the weather resistance of the modified polyurethane in reducing wear.
[0060] After 500 hours of xenon lamp aging, the tensile strength retention rates of Examples 1-3 (88%, 89%, 86%) were significantly higher than those of Comparative Examples 1-3 (75%, 80%, 82%), indicating that the modification process effectively inhibited oxidative degradation. The slightly lower retention rate of Example 3 may be due to a slightly weaker photothermal stability caused by a higher proportion of polyurethane. Comparative Example 1 (unmodified) showed the worst wet friction coefficient due to severe material swelling, resulting in the worst wear and aging retention rates. Comparative Example 2 (without grafting modification) had a worse wet friction coefficient (0.7 after water immersion) and wear (0.09) than the Examples, indicating that grafting modification enhanced hydrophilicity. Comparative Example 3 (with reduced filler) showed a slight decrease in hardness (53A) and resilience (62%), and a slight increase in wear (0.11), indicating that filler plays an important role in balancing hardness and wear resistance.
[0061] In summary, Examples 1-3, through the synergistic effect of modified polyurethane and silicone rubber, comprehensively outperformed the comparative examples in terms of hardness, elasticity, frictional stability, wear resistance, and aging resistance, verifying the effectiveness of the modification process. The differences between the different examples reflect the subtle influence of adjusting the raw material ratio on the performance. For example, the high hardness of Example 3 is due to the higher proportion of polyurethane, and the excellent resilience of Example 2 is due to the more balanced component design.
[0062] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. A highly elastic material, characterized in that, By weight percentage, its raw materials include: Modified polyurethane: 30-50%; Modified silicone rubber: 20-40%; Calcium carbonate: 10-20%; Dicumyl peroxide: 1-3%; 2-Mitrol-benzothiazole: 0.5-1.5%; N-Isopropyl-N'-Phenylene-p-phenylenediamine: 0.5-1%; Naphthenic oil: 1-5%; The method for preparing the modified polyurethane includes: A1, vacuum dehydrating polybutylene adipate at 110-115℃, cooling to 60-65℃ and then adding toluene diisocyanate and stirring to obtain a terminal isocyanate prepolymer; A2, then adding dimethylolpropionic acid to the prepolymer and heating to 80-85℃ to react; then adding triethylamine and adding deionized water while stirring to obtain an aqueous polyurethane dispersion; then adding methyl methacrylate, hydroxyethyl acrylate and potassium persulfate to the dispersion and heating to 70-75℃ to react.
2. The high-elasticity material according to claim 1, characterized in that, In step A1, the vacuum dehydration time is 2-3 hours; the stirring reaction time is 2-3 hours.
3. The high-elasticity material according to claim 1, characterized in that, In step A2, the temperature is raised to 80-85℃ and the reaction is carried out for 1-1.5 hours; the stirring speed is 8000-8500 rpm, and the reaction time is raised to 70-75℃ for 3-4 hours.
4. The high-elasticity material according to claim 1, characterized in that, The preparation method of the modified silicone rubber includes: adding methyl vinyl silicone rubber and precipitated silica into a mixer and mixing at 120-125°C; adding hydroxyl silicone oil and passing through a thin sheet; crushing the mixed rubber into particles; adding γ-glycidoxypropyltrimethoxysilane and ultrasonically dispersing at 80-85°C; and then mixing the modified silicone rubber particles with ethylenediamine and tetraethyl orthosilicate and vulcanizing at 150-155°C.
5. The high-elasticity material according to claim 4, characterized in that, The mixing time is 15-20 minutes; the number of thin passes is 5-6; the mixed rubber is crushed into 20-25 mesh particles; the ultrasonic dispersion time is 30-35 minutes; and the vulcanization time is 40-45 minutes.
6. A method for preparing a high-elasticity material according to any one of claims 1-5, characterized in that, step include: S1. Preheat the modified polyurethane at 80-85℃, and then add it together with the modified silicone rubber to a high-speed mixer for preliminary mixing. During the preliminary mixing process, add calcium carbonate and naphthenic oil in sequence and continue mixing. After the materials are mixed, transfer them to a two-roll mill for thin-pass processing. S2, then dicumyl peroxide, 2-thiol benzothiazole, and N-isopropyl-N'-phenyl-p-phenylenediamine are added to the open mill and refining. S3. Finally, transfer the compound to a flat vulcanizing machine for vulcanization, cool it to 20-25℃, and cut it into shape.
7. The preparation method according to claim 6, characterized in that, In step S1, the preheating time is 10-15 min; the speed of the high-speed mixer is 1000-1200 rpm, the initial mixing time is 5-10 min; the continued mixing time is 3-5 min; the roll temperature of the two-roll open mill is 80-85℃; the roll gap of the thin pass treatment is 1-1.2 mm, and the number of thin passes is 3-4 times.
8. The preparation method according to claim 6, characterized in that In step S2, the turning time in the open mill is 8-10 minutes.
9. The preparation method according to claim 6, characterized in that, In step S3, the vulcanization temperature in the flat vulcanizing machine is 160-165℃, the pressure is 10-12MPa, and the vulcanization time is 15-20min.
10. The application of a high-elasticity material according to any one of claims 1-5 or a high-elasticity material prepared by the preparation method according to any one of claims 6-9, characterized in that, The application of the high-elasticity material in anti-slip shoe soles.
Citation Information
Patent Citations
Heat-conductive thermoplastic dynamic vulcanized silicone rubber and preparation method thereof
CN109608866A
Nano-silica compatibilized silicone rubber / thermoplastic polyurethane blended elastomer and preparation method thereof
CN117247669A
Thermoplastic polyurethane elastomer-vinyl silicone rubber composite material as well as preparation method and application thereof
CN119463464A
Cited By
Silicone rubber anti-skid material for food shoes and preparation method of silicone rubber anti-skid material
CN122080646A